Delivery site preferences and associated factors among married women of Panauti Municipality, Kavrepalanchok district, Nepal - Pathak, Pratiksha; Manandhar, Naresh; Joshi, Sunil Kumar (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Maternal mortality is a top global developmental agenda. The main cause of being underutilization of available delivery services especially in a developing country like Nepal. Various socio-demographic, socio-cultural and health service-related factors affect the utilization of these services. Thus, the study aims to identify the delivery site preferences and its associated factors among the married women of Panauti municipality of Kavrepalanchok district.Method: A cross-sectional study was conducted among the married women between the ages of 15-49 y residing in Panauti municipality. The face-to-face interviews were conducted using semi-structured questionnaires. The statistical analysis was done using Statistical Package for Social Sciences (SPSS) version 21.Result: A total of 106 women of 15-49 y were included in the study. The proportion of institutional delivery among the participants was 68%. 90.6% of total participants would prefer health facility for their future deliveries; 7.5% were not sure about their preferences and very few (1.9%) preferred to deliver at home. The factors like knowledge regarding safe-motherhood program and age at marriage were found to be significantly associated with their delivery site preference (p